Multi-tiered marriage contracts in Nigeria and the need for reforming Nigerian Family Law - Imam-Tamim, Muhammad Kamaldeen (Ahmad Ibrahim Kulliyyah of Laws , International Islamic University Malaysia, 2015)
The study examines the practice of contracting multi-tiered marriage in Nigeria with a view to identifying the reasons why Nigerians celebrate this type of marriage; the legal problems associated with this kind of marriage; how they could affect the operation of family law in Nigeria and whether there is need to reform the Nigerian family law. The nature of the operation of the different systems of marriage in Nigeria is examined in order to show the distinctiveness of each system of marriage and explains how their rules are being applied in practice. The study identifies and highlights some of the legal problems that arise as a result of the celebration of multi-tiered marriage contract so as to determine whether they warrant the reform of family law in Nigeria. The study adopts a qualitative methodology and employs both doctrinal and non-doctrinal methods of legal research. For the doctrinal method, the study uses a qualitative content analysis by analysing contents of library and online based literature, statutes and case laws. For the non-doctrinal method, the study uses semi-structured interview and participant observation to collect empirical data from targeted participants who are selected through non-probablistic convenience and purposive sampling methods. It is found in the study that there are many lacunas in the operation of the three systems of marriage laws in Nigeria. While the unwritten nature of Islamic and customary laws is identified as a major lacuna, the obsoleteness and legal centric attitude of the Marriage Act 1914 are found as the major lacunas in the Act. Many provisions of the Act are also found to be incongruous with the rules of customary and Islamic laws both of which the people highly regard. It is also found that different social, cultural and legal factors contribute to why Nigerians celebrate multi-tiered marriage contracts. Analysis of judgments and responses from the interviews suggests that the contract of multi-tiered marriage is susceptible to legal problems that could affect the couples, the courts and the state. It is also discovered that the weak model of legal pluralism operates in Nigeria and this equally lures couples into contracting multi-tiered marriage. It is therefore suggested that there is a need for legal reform of Nigerian family law by upgrading the weak pluralism to strong model of legal pluralism. The study also proposes a 'pragmatic approach' for the reform exercise, which includes restatement of customary family law, codification of Islamic family law and amendment of the Marriage Act. The study concludes that if the reforms herein suggested are genuinely implemented, they will improve the family law in the country and thus may significantly reduce the rate of divorce. It will also make Nigeria a beacon of reform for other multi-cultural and multi-legal societies.